Effects of working gas pressure on zirconium dioxide thin film prepared by pulsed plasma deposition: roughness, wettability, friction and wear characteristics. (August 2017) - Berni, M.; Marchiori, G.; Gambardella, A.; Boi, M.; Bianchi, M.; Russo, A.; Visani, A.; Marcacci, M.; Pavan, P.G.; Lopomo, N.F.
Abstract: In joint arthroplasty one of the main issues related to the failure of prosthetic implants is due to the wear of the ultra-high molecular weight polyethylene (UHMWPE) component. Surface treatments and coatings have been recognized as enhancing methods, able to improve the tribological properties of the implants. Therefore, the main objective of this work was to investigate the possibility to fabricate yttria-stabilized zirconia (YSZ) coatings on a metal (AISI 316-L) substrate by means of Pulsed Electron Deposition, in order to improve the tribological behavior of the polymer-metal coupling, by reducing the initial wear of the UHMWPE component. In order to optimize the coating characteristics, the effects of working gas pressure on both its morphological and tribological properties were analyzed. Morphological characterization of the films was evaluated by Atomic Force Microscopy (AFM). Coating wettability was also estimated by contact angle (CA) measurement. Tribological performance (coupling friction and wear of UHMWPE) was evaluated by using a ball-on-disc tribometer during highly-stressing tests in dry and lubricated (i.e. NaCl and serum) conditions; friction and wear were specifically evaluated at the initial sliding distances - to highlight the main effect of coating morphology - and after 100 m - where the influence of the intrinsic materials properties prevails. AFM analysis highlighted that the working pressure heavily affected the morphological characteristics of the realized films. The wettability of the coating at the highest and lowest deposition pressures (CA ~ 60°, closed to substrate value) decreased for intermediate pressures, reaching a maximum CA of ~ 90°. Regarding tribological tests, a strong correlation was found in the initial steps between friction coefficient and wettability, which decreased as the distance increased. Concerning UHMWPE wear associated to coated counterpart, at 100 m a reduction rate of about 7% in dry, 12% in NaCl and 5% in presence of serum was obtained compared to the uncoated counterpart. Differently from what highlighted for friction, no correlation was found between wear rate and morphological parameters. These findings, in agreement with literature, underlined the effect of the deposition pressure on the morphological properties, but suggested that physical characteristics are influenced too. Further research on the deposition process will be required in order to improve the tribological performance of the coating at long distances, addressing – above all - orthopedic applications. Highlights: Pulsed Electron Deposition (PED) is proposed as an effective coating method. Ceramic films were deposited on AISI 316-L to reduce UHMWPE wear in joint prostheses. Films were characterized by morphological and tribological analysis. Results suggested that the working gas pressure can be use to tailor the structural behavior of the films in response to specific requirements.